Association of insulin resistance surrogates with disease severity and adverse outcomes in chronic thromboembolic pulmonary hypertension: a multicenter cohort study - Luyang Gao; Sicheng Zhang; Sicong Li; Manqing Luo; Ping Lin; Zhihui Zhao; Qing Zhao; Tao Yang; Anqi Duan; Yijia Wang; Qi Wang; Qin Luo; et al. (Cardiovascular Diabetology)
Abstract Background Chronic thromboembolic pulmonary hypertension (CTEPH) is a severely progressive disease that leads to right heart failure and death. Previous studies have shown that diabetes and insulin resistance (IR) are closely related to pulmonary hypertension, but the role of IR in patients with CTEPH remains unexplored. In this study, we investigated the relationship between four insulin resistance indices and disease severity, hemodynamic parameters, and adverse outcomes in patients with CTEPH. Methods We conducted a multicenter, retrospective cohort study involving 516 patients diagnosed with CTEPH between January 2013 and December 2022. The metabolic score for IR (METS-IR), triglyceride to high-density lipoprotein cholesterol (TG/HDL-C) ratio, triglyceride and glucose (TyG) index, and triglyceride-glucose-body mass (TyG-BMI) index were used to quantify IR levels in patients with CTEPH. The primary endpoint events were clinical worsening. Multivariable Cox regression, restricted cubic splines, and receiver operating characteristic analyses were used to evaluate the predictive value of surrogates for IR. Results Compared with in low to intermediate-low risk patients, the METS-IR (36.2 ± 6.7 vs. 37.7 ± 8.7, p = 0.038) and TyG-BMI index (204.0 ± 36.2 vs. 212.6 ± 46.5, p = 0.022) were significantly increased in high to intermediate-high risk patients. METS-IR correlated with markers of disease severity, such as World Health Organization functional class, 6-minute walk distance, and N-terminal pro-brain natriuretic peptide levels. During a mean of 2.5 years’ follow-up, 110 participants experienced all-cause death or worsening condition. METS-IR independently predicted clinical worsening (hazard ratio: 1.27; 95% confidence interval 1.06–1.53 per 1.0-standard deviation increment, p = 0.009) after fully adjusting for covariates. Adding METS-IR to the COMPERA 2.0 risk score significantly improved its predictive ability, reclassification and discrimination ability. Conclusions METS-IR is an independent predictor of clinical worsening in patients with CTEPH. It offers a convenient marker for assessing disease severity and long-term outcomes in clinical risk assessment.